Efficacy of Lactic Acid Bacteria as a Biocontrol Agent against Anthracnose (Persea americana Miller) Decay in Avocado (Persea americana) cv Fuerte Fruit - Azola Siwaphiwe Mpeluza; Stephen Abiola Akinola; Tinotenda Shoko; Fabienne Remize; Dharini Sivakumar (Agriculture, 2023)
Anthracnose disease is still a threat to avocado fruit quality, and the use of fungicide (Plochloraz®) for its control has generated safety concerns that necessitate the search for alternatives. Therefore, the efficiency of lactic acid bacteria (LAB) isolated from fresh fruits and vegetables as biocontrol agents against Colletotrichum gloeosporioides was investigated in this study. Weissella cibaria 21 (LAB 21), Leuconostoc pseudomesenteroides 56 (LAB 56), Weissella confusa 17 (LAB 17), Lactiplantibacillus plantarum 75 (LAB 75), and Lactiplantibacillus plantarum 171 (LAB 171) were evaluated in vitro as potential biocontrol agents to replace the Prochloraz® that is currently used in susceptible avocado (Persea americana Miller) Fuerte fruit. To confirm the biocontrol activity of the selected LAB strains, the antagonistic growth, spore germination, LAB recovery, nutrient competition, acid tolerance, and biofilm formation were assessed. In fruit treated with a LAB cell suspension, curatively inoculated with C. gloeosporioides, or naturally infected avocado cv Fuerte fruit, the epicatechin content and expression of defense-related genes (PAL, LOX, AVFADl 2–3, AVFAEL, and FLS) were compared with Prochloraz® and sterile water (control) treatments. With LAB 56, LAB 75, and LAB 21, significant inhibition of radial mycelial growth (MGI) (>90%) and spore germination (100%) was observed similar to those due to Prochloraz®. The MGI increased with a reduction in nutrient concentration. LAB strains reduced anthracnose disease incidence and severity compared with Prochloraz® and were the highest in LAB 21 and LAB 56. The LAB 21 and LAB 56 strains produced strong biofilms against C. gloeosporioides. In contrast to LAB 56, the control, and Prochloraz®, and LAB 21 had the highest epicatechin content (406 mg/g) and upregulated the PAL, AVFADl 2–3, AVFAEl, and FLS genes, thereby reducing the incidence of anthracnose in avocado fruit. As a result, LAB 21 suspensions can be used as an alternative to Prochloraz® in the control of anthracnose disease.